TINJAUAN HUKUM TERHADAP PEMBEBASAN BERSYARAT NARAPIDANA DI LEMBAGA PEMASYARAKATAN KELAS II A BULUKUMBA: LEGAL REVIEW ON THE TERMINAL RELIEF OF INCIDENTS IN CLASS II A PENALTY INSTITUTIONS BULUKUMBA - Hasan, Asriani; Madiong, Baso; Oner, Basri (Clavia, 2022)
This study aims to determine 1) The implementation of parole for psioners in correctional institution class II A Bulukumba, 2) Factoes that prevent psioners from getting parole outside the penitentiary. The research uses the type of empirical normative research, the type of data used is primary and secondary data, data from primary materials, namery data obtained directly through information using interview techniques with the correctional institutions clas II A bulukumba, anddata from secondary materials refer to laws, book, journals and data from correctional institutions class II A Bulukumba relating to the problems studies as awll as sources and information obtained from the result of questionnaires with prisoners in correctional institutions clas IIA Bulukumba. The results of thisstudy indicate that 1) Implementationof parole in correction institutional class II A Bulukumba the 2021 period its been optimized its running well although in itsimplementation there are still obstacles,2)The inhibiting factors are external and internal factors, including the guarantor from thefamily of the inmate whose where abouts are unknown and the existence of psioners who violate disxipline in the correctional institution whih causes the inmate to fail to get parole.